Occurrence of high altitude cerebral edema (hace) and high altitude pulmonary edema (HAPO) simultaneously at 12000 ft: a rare phenomen - Kumar, Dharmendra; Rath, T. K.; Verma, L. C. (International Journal of Advances in Medicine, 2018)
High altitude cerebral edema (HACE) and High altitude pulmonary edema (HAPO) are the most dreaded complications related to high altitude. Authors managed a case of HACE and HAPO simultaneously set at unusually low height (1200 ft) in a patient. The altitude was not too much to develop these comorbidities as studied earlier. Relationship with altitude was immaterial in our case. However, rapid ascent without proper acclimatisation, young and tender age, male sex and smoking were associated contributing factors. He was managed with standard protocol and descent to lower altitude.